Thermodynamic Interpretation of the Fragmentation Phenomenon in Nanopores - Vakili-Nezhaad, G.R.; Ali Mansoori, G. (Asian Journal of Chemistry, 2010)
Based on the new van der Waals equation of state for confined fluids in nanopores, an interesting thermodynamic interpretation has been made for the fragmentation phenomenon of the confined fluids in the nanopores such as carbon nanotubes. The new concept of anisotropic fugacity has been introduced in this work.